Impact of COVID-19 on the global sporting industry and related tourism - Nhamo, G.; Dube, K.; Chikodzi, D. (Counting the Cost of COVID-19 on the Global Tourism Industry, 2020)
Infectious diseases present an omnipresent threat to the health and safety of the global community. In 2020, the COVID-19 pandemic that began in China in 2019 swept around the world imposing unprecedented impacts on all the sectors of the world economy. The multibillion-dollar sports tourism industry was hit hard. This chapter unravels the impacts of COVID-19 on sporting events and, by default, sporting tourism. Such information is key for the industry to develop resilience against future pandemics and other natural disasters. Document and critical discourse analysis was used in gathering and analysing data. The findings show that most sporting events were either cancelled or postponed during the peak of the pandemic because of COVID-19 containment measures across the world, such as travel bans and port closures. Many sports governing bodies were also bankrupted and left in financial distress. Individual athletes lost income as their salaries were reduced or completely cut. Sponsors, betting firms, broadcasters and others in the sports value chain also incurred huge losses during this period. Among the key events affected were the 2020 Olympics, football leagues, golf, cricket, marathons, rugby and tennis. As such, there was a need for bailout packages and seeking alternatives for the sports industry to recover from the shock. This chapter recommends post-COVID-19 reviews of the sports industry and putting in place alternative future intervention measures for similar pandemics and other disasters.